Bimbingan Teknis Penanganan Kasus Hukum Koperasi: Pentingnya Sertifikasi Kompetensi Pengurus dan Pengawas Koperasi dalam Mengelola Kegiatan Usaha Koperasi Melalui Uji Kelayakan dan Kepatutan Lembaga Sertifikasi - Rosti Setiawati (LPPM Universitas Koperasi Indonesia, 2023)
Training with material on the Importance of Competency Certification for Cooperative Managersand Supervisors in Managing Business Activities Conducted by Cooperatives Through Fit andProper Tests from Certification Institutions in charge of Cooperatives is carried out so thatparticipants can better understand the importance of Managers and Supervisors having competencycertification. Thus they understand that they are not just being Management and Supervisors ofCooperatives, but they need to take a certified competency test so that they carry out their dutieswith full responsibility and comply with applicable rules, and have their competency recognized.Output This activity is so that the 30 Management and Supervisors of KSP and USP Cooperativesthroughout West Java Province who participate in this Bimtek can carry out their duties carefullyand be responsible for Cooperative members as depositors and borrowers of funds. The outcome of this activity is so that the Management and Supervisors of Cooperatives, especially Cooperatives engaged in savings and loan activities (KSP/USP Cooperatives) throughout West Java have certified competencies. Achieve the objectives of this training activity, it is carried out through anexplanation of the importance of certification, duties, and obligations as Managers and Supervisors followed by examples of solving relevant cases, thus inviting discussion to be able to produce solutions to various problems that exist in Managers and Supervisors in carrying out their duties.